Β‐Carotene attenuates LPS‐induced rat intestinal inflammation via modulating autophagy and regulating the JAK2/STAT3 and JNK/p38 MAPK signaling pathways. Issue 1 (4th November 2020) - Yang, Yu; Li, Ruonan; Hui, Junnan; Li, Lingqian; Zheng, Xin
Abstract: Inflammation is a protective response of the immune defense system and inflammatory response could be regulated by autophagy. β‐Carotene has shown anti‐inflammatory potential. However, whether β‐carotene could alleviate rat intestinal inflammation by modulating autophagy and its anti‐inflammation underlying mechanisms remain unknown. In this study, we found that β‐carotene significantly reduced ( p  < .05) the production of nitric oxide (NO), prostaglandin (PG)E2, tumor necrosis factor (TNF)‐α, and interleukin‐1β (IL‐1β) levels by the Griess reaction and enzyme‐linked immunosorbent assay (ELISA), and we found that β‐carotene significantly suppressed ( p  < .05) the mRNA expression levels of IL‐1β and TNF‐α by RT‐PCR. In addition, H&E staining revealed that β‐carotene could improve intestinal morphology and cell morphology. Furthermore, the levels of signaling proteins of microtubule‐associated protein light chain 3 (LC3), AKT, Janus kinase 2/signal transducers and activators of transcription 3 (JAK2/STAT3), nuclear factor‐kappa B (NF‐κB), and c‐Jun N‐terminal kinase (JNK)/p38 mitogen‐activated protein kinase (MAPK) were detected by Western blot analysis. We found that β‐carotene significantly attenuated ( p  < .05) the related signaling proteins activated by lipopolysaccharide (LPS) stimulation in rats. Moreover, this conclusion was also verified in intestinal epithelial cell (IEC)‐6. 3‐Methyladenine (3‐MA) is widely used as inhibitor of autophagy via its inhibitory effect on class III PI3K. Simultaneously, pretreatment of 3‐MA suppressed the inhibiting effects of β‐carotene on the related signaling proteins. This study demonstrates that β‐carotene could attenuate the LPS‐induced intestinal inflammation in rats via modulating autophagy and regulating the JAK2/STAT3 and JNK/p38 MAPK signaling pathways. We also found the same phenomenon when we verified the results with the IEC‐6 cells. These findings provide new insights into improving the nutritional value of basic diets and enhancing immune performance. Practical applications: β‐Carotene is a generally acknowledged natural carotenoid nutrient that exhibits provitamin A activity, and it is widely found in fruits or vegetables. Our study provide a new insight into the anti‐inflammatory mechanism of β‐carotene. Treatment with β‐carotene can be used for the beneficial effect against LPS‐induced inflammation damage. This study not only lays the foundation for the related research on the anti‐inflammatory properties of β‐carotene in vitro and in rat models, but also holds important significance in the field of food. Abstract : β‐Carotene exhibits anti‐inflammatory activities in vitro and in vivo. β‐Carotene could reduce the production of inflammatory factors. β‐Carotene may exert anti‐inflammatory effects via modulating autophagy and regulating the JAK2/STAT3, and JNK/p38 MAPK signalling pathways.